Vague soft R-subgroups and vague soft quotient near rings - Sushama Vijaykumar Patil; J.D. Yadav (Journal of Hyperstructures)
The purpose of the present paper is to throw light on the study of vague soft R-subgroup over near-ring R. We have defined vague soft R-subgroup over a near-ring. By using quotient near-ring we have defined vague soft quotient near-ring. Also, we have investigated operations of vague soft R-subgroup over a near-ring and vague soft quotient near-ring.